Recurrent Wheezing: Prevalence and Associated Factors in Infants from Buenos Aires City, Argentina [Sibilancias Recurrentes: Prevalencia y Factores Asociados en Lactantes de Buenos Aires, Argentina] - Mallol-Villablanca, E (Masson-Doyma Mexico, S.A., 2017)
Background The episodes of bronchial obstruction at early age constitute a frequent problem in Pediatrics. The aim of this study was to evaluate the prevalence of recurrent wheezing in infants in Buenos Aires City, as well as to identify any associated factors. Methods Cross-sectional study performed from 2011 to 2012 in the Children Hospital Ricardo Gutiérrez, Buenos Aires City, as part of the International Study of Wheezing in Infants. A validated questionnaire was applied to parents of infants aged between 12 and 15 months. The prevalence of wheezing, mostly the recurrent episodes (three or more), and their probable associated factors were evaluated. Data were statistically analyzed with χ 2 , Fisher s test, binary and logistics multiple regression analysis. The significance level was 0.05. Results Over 1063 infants, 58.9% (confidence interval (CI) 95% 55.9-61.9) presented at least one episode of wheezing and 26.3% (CI95% 23.8-29.9) three or more episodes (recurrent wheezing). Risk factors associated to wheezing were male gender (p = 0.001), six or more episodes of cold during the first year of life (p < 0.0001), age at first cold < 4 months (p < 0.0001); pneumonia (p < 0.0001) and smoking during pregnancy (tobacco) (p = 0.01). For recurrent wheezing, risk factors we considered as six or more episodes of cold during the first year of life (p < 0.0001), early (< 4 month of age) onset wheezing (p < 0.0001) and nocturnal wheezing (p < 0.0001). Conclusions The prevalence of recurrent wheezing among infants in Buenos Aires Ciy was high (26.3%). Some identified associated factors can be preventable. © 2017 Hospital Infantil de México Federico Gómez